King of jazz - Ager, Milton 1893-1979 (<<The>> Criterion Collection, 2018)
"Florence Ziegfeld, der große Revue-Arrangeur, träumt im Himmel von einer Show großen Stils, die alle Talente seiner Epoche noch einmal vereint: Ballett, Songs, Sketches und eine Fülle von Top-Stars in einer opulenten nostalgischen Retrospektive auf das amerikanische Show-Business der 40er Jahre." [filmdienst.de]
Original: USA 1930
Blu-ray special edition features: new 4K digital restoration by Universal Pictures, with uncompressed monaural soundtrack ; new audio commentary featuring jazz and film critic Gary Giddins, music and cultural critic Gene Seymour, and musician and bandleader Vince Giordano ; new introduction to the film by Giddins ; new interview with musician and pianist Michael Feinstein ; four new video essays by authors and archivists James Layton and David Pierce on the development and making of "King of jazz" ; deleted scenes and alternate opening title sequence ; "All americans", a 1929 short film featuring a version of the "Melting pot" number that was restaged for "King of jazz" ; "I know everybody and everybody’s racket", a 1933 short film featuring Paul Whiteman and his orchestra ; two Oswald the lucky rabbit cartoons from 1930, featuring music and animation from "King of jazz" ; plus: An essay by critic Farran Smith Nehme
Bildformat 1.37:1
Keywords: Film; Blu-Ray-Disc